ความคิดเห็นของนักศึกษาสาขาการบัญชี คณะบริหารธุรกิจ มหาวิทยาลัยเชียงใหม่ ต่ออาชีพผู้สอบบัญชี - นุชชรีพร คอทอง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This independent study aims to investigate opinions of accounting students of faculty of Business Administration, Chiang Mai University towards auditor career. The study process include data gathering via questionnaire regarding motivation factors wherein the most important social motives for career are hygiene and factors relating to individual preferences.The questionnaire was answered by 208 students studying in 4th year from the faculty of Business Administration, Chiang Mai University. The data was analyzed statistically resulting in frequency, percent and mean data sets illustrated as follows; The majority of studied groups are females with 2.76 - 3.24 GPA. Their family incomes are more than 50,000 Baht with 4 - 6 family members living in northern region of Thailand. People influencing their choice of career preference are themselves. Their parents or guardians' career is majorly self-employed. Most respondents need to be majoring as auditor because this is the relevant field of study and the career that respondents should not be majoring is accountants. The majority of student groups are concerned about hygiene factors as their secondary significant choice of career preference decision factors. The hygiene factors categorizing in high levels include co-worker relations, working status, income, organization administration policies, working condition, secured career and self-being factor. The majority of student groups are concerned about motivating factors as their secondary significant choice of career preference decision factors. The motivating factors categorizing in highest level include responsibility, career development, superior opportunity, admiration, achievement and occupational characteristic. The majority of student groups are concerned about hygiene factors as their moderate significant choice of career preference decision factors as self-being factor that concerned auditor will not have time to be with family and working hours will have an effect in private life. And motivating factors The majority of student group concern as auditor career not have admiration due to this career frequently have job change and needed to have a retire. As for suggestion, The majority of student group suggested that audits firm or agencies should give the correct data and helpful for their choice of auditor career and also make a confidence in internal and external factors of auditor career.